2021
DOI: 10.1101/2021.02.22.432328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-order interactions maintain or enhance structural robustness of a coffee agroecosystem network

Abstract: The capacity of highly diverse systems to prevail has proven difficult to explain. In addition to methodological issues, the inherent complexity of ecosystems and issues like multicausality, non-linearity and context-specificity make it hard to establish general and unidirectional explanations. Nevertheless, in recent years, high order interactions have been increasingly discussed as a mechanism that benefits the functioning of highly diverse ecosystems and may add to the mechanisms that explain their persiste… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Reviews and empirical studies suggest that, by initiating the phenotypic response of a resource or a competitor, a modification species can cause strong effects on a pairwise interaction, consequently leading to strong effects at population, community, and ecosystem levels [5,7,35]. Theoretical and empirical studies found that HOIs increase the robustness of food webs [4,[11][12][13], and the structure of two interactive HOIs can stabilize biodiversity-rich ecological networks [11]. With such a recognition, however, most theoretical and empirical…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews and empirical studies suggest that, by initiating the phenotypic response of a resource or a competitor, a modification species can cause strong effects on a pairwise interaction, consequently leading to strong effects at population, community, and ecosystem levels [5,7,35]. Theoretical and empirical studies found that HOIs increase the robustness of food webs [4,[11][12][13], and the structure of two interactive HOIs can stabilize biodiversity-rich ecological networks [11]. With such a recognition, however, most theoretical and empirical…”
Section: Discussionmentioning
confidence: 99%
“…interaction modification, in contrast to interaction chain, [2]), has been widely recognized in ecological studies [3][4][5][6][7][8][9][10]. Yet, studies remain in theoretical explorations of large communities focusing on diversity and stability [4,[11][12][13], or consumption coefficients in small or large ecological communities with only one degree HOIs (i.e. one additional species modifying one pair-wise interaction) [5,7,8,10,14,15].…”
Section: Introductionmentioning
confidence: 99%